EFFECT OF ON SEVERITY OF SEEDLING ROT TRICHODERMA HARZIANUM OF CHILLI CAUSED BY RHIZOCTONIA SOLANI (Journal of Plant Disease Sciences, 2017)
Chilli ( L.) is Capsicum annuum  temperate annual plant commonly cultivated  for its vegetable purpose and dry chilli as  spice of commerce. It is good source for  culinary uses, arthritis pain, diabetic  neuropathy and headache. Chilli is a rich  source of vitamin C, B, B , carotene 6 (provitamin A), high in potassium (K),  magnesium (Mg) and iron (Fe). In India, it is  an important cash crop, which is grown for the  both domestic and export market. India is the  largest producer of chilli occupying about  0.82 million hectare area in the world  followed by China (4 lakh tonnes) Raja et al. (2013). Among the biotic stresses, seedling  rot of chilli caused by , is Rhizoctonia solani the most serious disease and has national  importance as it affects the seedling during the  early stages. It causes rot/necrosis of the  seedling and rottening of the plants. Chilli is  also affected by various fungi . viz Anthracnose ( spp.) Collectotrichum  Cercospora leaf spot ( ), Cercospora capsici Bacterial leaf spot (Xanthomonas campestris  pv ), viruses TSWV (TSW virus). vesicatoria Among the fungal diseases, damping off  disease of seedling as well as root and stem rot  in young transplants of chilli caused by  Rhizoctonia solani is major soil borne disease  causing huge economic losses in chilli.  Antagonistic fungi and bacteria; therefore,  assumes great significance, among the  antagonistic fungi, Trichoderma harzianum  has shown promise as a biocontrol agent for R.  solani et al Kumar . (2012). A field experiment  to test the effect of on severity of Trichoderma seedling rot of chilli (C L.) apsicum annuum caused by on growth and Rhizoctonia solani yield parameters was investigated at our  adopted village Banda, district Katni, for  suppressing and seedling rot of chilli  promoting healthy plant growth and fruit size. The field trial was laid out with 6 treatments
Keywords: Chilli, Trichoderma harzianum, Iprodione, Carbendazim, Mancozeb, Chlorothalonil, Rhizoctonia solani.